Influence of the echocardiographic score and not of the previous surgical mitral commissurotomy on the outcome of percutaneous mitral balloon valvuloplasty - Peixoto,Edison C. Sandoval (2001)
OBJECTIVE: To evaluate prior mitral surgical commissurotomy and echocardiographic score influence on the outcomes and complications of percutaneous mitral balloon valvuloplasty. METHODS: We performed 459 complete mitral valvuloplasty procedures. Four hundred thirteen were primary valvuloplasty and 46 were in patients who had undergone prior surgical commissurotomy. The prior commissurotomy group was older, had higher echo scores, and a tendency toward a higher percentage of atrial fibrillation. RESULTS: When the groups were compared with each other, no differences were found in pre- and postprocedure mean pulmonary artery pressure, mean mitral gradient, mitral valve area, and mitral regurgitation . Because we found no significant differences, we subdivided the entire group based on echo scores, those with echo scores <=8 and those with echo scores >8 the mitral valve area being higher in the <=8 echo score group 2.06±0.42 versus 1.90±0.40cm² (p=0.0090) in the >8 echo score group. CONCLUSION: Dividing the groups based on echo score revealed that the higher echo score group had smaller mitral valve areas postvalvuloplasty.